1999
DOI: 10.1165/ajrcmb.20.5.3243
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Interleukin-8 Production by Cystic Fibrosis Airway Epithelial Cells

Abstract: The acquisition of Pseudomonas aeruginosa in the airways of patients with cystic fibrosis (CF) is the initial event leading to bronchiectasis and lung disease. Although the host factors that permit initial airway colonization are largely unknown, recent studies suggest that secretion of interleukin (IL)-8 by airway epithelia and local recruitment of neutrophils is the final pathway in a pulmonary cytokine network. To determine whether differences in cytokine production exist between normal and CF airway epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
24
2
Order By: Relevance
“…We report that P. aeruginosa elicited a more robust increase in cytokine and chemokine expression (e.g., IL-8, CXCL1, CXCL2, and TNF-␣) in CFBE-wt-CFTR cells compared with CFBE-⌬F508-CFTR cells. These data add to a growing body of evidence revealing that the inflammatory response of human airway epithelial cells expressing wt-CFTR and ⌬F508-CFTR to P. aeruginosa is model dependent, even when considering matched cell lines and human airway epithelial cells in primary culture (4,6,8,16,18,22,26,28,31,37,39,41). Taken together with other published studies, our data demonstrate that there is no compelling evidence to support the view that mutations in CFTR induce a hyperinflammatory response in human airway epithelial cells in vivo.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…We report that P. aeruginosa elicited a more robust increase in cytokine and chemokine expression (e.g., IL-8, CXCL1, CXCL2, and TNF-␣) in CFBE-wt-CFTR cells compared with CFBE-⌬F508-CFTR cells. These data add to a growing body of evidence revealing that the inflammatory response of human airway epithelial cells expressing wt-CFTR and ⌬F508-CFTR to P. aeruginosa is model dependent, even when considering matched cell lines and human airway epithelial cells in primary culture (4,6,8,16,18,22,26,28,31,37,39,41). Taken together with other published studies, our data demonstrate that there is no compelling evidence to support the view that mutations in CFTR induce a hyperinflammatory response in human airway epithelial cells in vivo.…”
Section: Discussioncontrasting
confidence: 47%
“…However, even studies on matched cell lines do not produce consistent results. For example, studies on IB3-1 (⌬F508/W1282X) and S9 cells (IB3-1 cells complemented with wt-CFTR) demonstrate that P. aeruginosa elicits a more robust increase in IL-8 production in IB3-1 CF cells than in wt-CFTR-corrected S9 cells (1,10), whereas studies on other matched cell lines reveal that, when challenged with P. aeruginosa, CF cells actually produce less IL-8 than non-CF cells, contrary to the generally accepted view that CF mutations enhance the inflammatory response of airway epithelial cells to P. aeruginosa (16,22,31).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The vector control cell line CFT1-LC3 was obtained by transfection of CFT1 cells with a retroviral vector encoding ␤-galactosidase (␤gal), and CFT1-LCFSN was obtained by transfection of CFT1 with wild-type CFTR (13). The three cell lines were grown in Ham's F-12 medium (GIBCO) supplemented with 10 g͞ml insulin (GIBCO), 0.5 g͞ml hydrocortisone (Sigma), 3.75 g͞ml endothelial cell growth supplement (Sigma), 25 ng͞ml epidermal growth factor (Sigma), 3 ϫ 10…”
Section: Cellsmentioning
confidence: 99%
“…In a mouse CF model, instillation of P. aeruginosa embedded in agar beads results in increased production of inflammatory cytokines in CF animals compared with similarly treated wild-type controls (15). Recent studies have demonstrated that CF epithelia are not responsible for the overexpression of these proinflammatory cytokines (16).…”
mentioning
confidence: 99%